2018
DOI: 10.1002/2017wr022168
|View full text |Cite
|
Sign up to set email alerts
|

Using In‐Situ Optical Sensors to Understand the Biogeochemistry of Dissolved Organic Matter Across a Stream Network

Abstract: The advent of high‐frequency in situ optical sensors provides new opportunities to study the biogeochemistry of dissolved organic matter (DOM) in aquatic ecosystems. We used fDOM (fluorescent dissolved organic matter) to examine the spatial and temporal variability in dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) across a heterogeneous stream network that varies in NO3− concentration. Across the ten study streams fDOM explained twice the variability in the concentration of DOC (r2 = 0.82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 60 publications
2
16
0
1
Order By: Relevance
“…Model predictions were also sensitive to inclusion of FDOM and pH. FDOM is an effective proxy for dissolved DOC (e.g., Snyder et al, 2018; Wymore et al, 2018), which our analysis also suggested. However, K + was similarly sensitive to FDOM, which is not intuitive.…”
Section: Discussionsupporting
confidence: 64%
“…Model predictions were also sensitive to inclusion of FDOM and pH. FDOM is an effective proxy for dissolved DOC (e.g., Snyder et al, 2018; Wymore et al, 2018), which our analysis also suggested. However, K + was similarly sensitive to FDOM, which is not intuitive.…”
Section: Discussionsupporting
confidence: 64%
“…FDOM H export fluxes were 90–187% higher than that of the 2014 and 2015 pre‐dry seasons after El Niño reached its strongest phase. Similar to other river and estuarine systems (Bauer & Bianchi, 2011; Saraceno et al, 2009; Wymore et al, 2018), there was a significant correlation between FDOM H and DOC in the Jiulong River Estuary (Figure S8; Guo et al, 2011). Thus, it is expected that the export pattern of DOC from Jiulong River resembles that of FDOM H .…”
Section: Discussionsupporting
confidence: 76%
“…The excitation‐emission wavelength of current commercial FDOM sensors represents humic‐like FDOM (FDOM H ) components, which are considered a good proxy for the terrestrial DOM fraction (Coble, 1996; Guo et al, 2014; Yang et al, 2019). In many aquatic systems, FDOM is highly correlated with DOC (Guo et al, 2011; Webb et al, 2018), suggesting that FDOM sensors provide an effective tool for monitoring watershed DOM dynamics and export (Shultz et al, 2018; Wymore et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOM consists of dissolved organic carbon (DOC), N, P, and other nutrients in molecular forms ranging from complex molecules to simple compounds. The molecular composition of the DOM influences its biodegradability and photoreactivity, affecting its persistence in the ecosystem and influence on nutrient cycles (Wymore et al, 2018;Harjung et al, 2019). In addition to biodegradability incubations (details below), we calculated two optical proxies of DOM composition: specific ultra-violet absorbance at 254 nm (SUVA 254 ) and the spectral ratio (S R ) of slopes within the 275-290 and 350-400 nm range (Weishaar et al, 2003;Helms et al, 2008;Vonk et al, 2015).…”
Section: Proxies Of Biogeochemical Transformationmentioning
confidence: 99%